Study of Potential Failure Points of Ventilation Shafts - Nurbol Bakhtybaev; Ravil Mussin; Rustem Alzhanov; Sholpan Zeitinova; Oraz Abil (Journal of Studies in Science and Engineering, 2025)
This study aims to identify potential failure zones in the ventilation shaft to enhance its safety and durability. The study involved parameter measurement, software modeling, finite element analysis, and analytical calculations. The study confirmed that loose ventilation pits pose a potential operational hazard. The creation of technological regulations for their fixation, including their specifics, proved necessary to ensure safety. The analysis of inelastic deformation zones using RocData and RS3 software revealed that RocData allowed a successful transition from laboratory rock characteristics to massive rock characteristics. At the same time, RS3 provided effective numerical modeling of the stress-strain state of rocks using the finite element method. The analysis results identified the areas of the ventilation shaft that are most vulnerable to failure under various loads, including wind forces, snow loads, and seismic activity. The application of a comprehensive approach, including assessment of the current condition, determination of load types, modeling and analysis of structural integrity, as well as the development of safety and strengthening measures, allowed us to formulate effective strategies for maintaining the safety of the ventilation shaft. Regular monitoring and inspection ensure the reliability and durability of the infrastructure. Based on the identified vulnerable areas, recommendations are developed to strengthen and protect the shaft structure. Proposed safety measures may include changing materials, adding reinforcements, or modifying the structure's geometry.